2014
DOI: 10.2174/1874325020140515002
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Failure Among Infected Periprosthetic Total Hip Arthroplasty Patients

Abstract: Two-stage revision has been shown to be the most successful treatment in eradicating deep infection following total hiparthroplasty. We identified 62 patients treated by a two-stage revision. We defined “successful revision” as negative intraoperative cultures and no further infection-related procedure. We defined “eradication of infection” on the basis of negative cultures and clinical diagnosis at least one year after 2nd stage procedure. After a mean follow up of 2.7 years, eradication of the infection was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Total hip arthroplasty (THA) has become the gold standard treatment for patients with end stage arthritis [ 1 ]. Multiple studies have demonstrated that THA improved the physical function and quality of life significantly [ 2 - 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Total hip arthroplasty (THA) has become the gold standard treatment for patients with end stage arthritis [ 1 ]. Multiple studies have demonstrated that THA improved the physical function and quality of life significantly [ 2 - 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous patients with end stage arthritis treated with cemented total hip arthroplasty (THA), and the number is rapidly increasing [ 1 - 4 ]. Almost 1 million of THA are implanted worldwide annually, with a predicting increase of 174% to nearly 600,000 THA procedures annually by 2030 in the United States [ 5 - 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…2012 [ 26 ] Austria 2000 to 2008 25 to 84 a 56.8 67.0 Cementless Spacer 1 44 Two-stage Schwarzkopf et al . 2014 [ 27 ] USA 2001 to 2011 62.3 46.9 32.4 Cemented Spacer 3 62 Two-stage Zeller et al . 2014 [ 28 ] France 2002 to 2010 71.0 58.0 41.6 Cementless NA 6 157 One-stage NA, not applicable; NS, not stated; Both, some participants had cemented re-implantation and others cementless.…”
Section: Methodsmentioning
confidence: 99%